INOVASI SOFTWARE MATEMATIKA LIMIT DAN INTEGRAL BAGI CALON GURU - Retno Marsitin; Nyamik Rahayu Sesanti (JPM PAMBUDI, 2023)
This community service activity aims to improve the skills of prospective mathematics teachers on limit and integral mathematical software. The activities include training in mathematical software innovation on limit and integral. The training materials include the definition of mathematical software, installation, use of mathematical software in the form of maple math, material delivery, interactive dialogue, presentations, and evaluation. This is an indicator of the successful implementation of community service activities. The results of community service activities are mathematical software innovation modules on limit and integral. The module describes the use of mathematical software on limits and integrals for mathematical calculations and graphs. This community service activity received positive responses, and the results of prospective mathematics teachers’ presentations in applying mathematical software on limits and integrals were very good.